THE DIFFERENCES OF APOPTOSIS EFFECTS BETWEEN COMBINATION OF MELOXICAM WITH GEMCITABINE-CARBOPLATIN CHEMOTHERAPY COMPARED TO GEMCITABINE-CARBOPLATIN CHEMOTHERAPY ALONE IN UROTHELIAL CARCINOMA CULTURE CELLS - Nugroho, Ananta Cahyo; Hakim, Lukman; Dajtisoesanto, Wahjoe; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: To determine the differences of apoptosis effect between the combination of meloxicam and gemcitabine-carboplatin compared to gemcitabine-carboplatin alone as the standard of chemotherapy care in urothelial carcinoma culture cells. Material & Methods: This research is an in vitro experimental using human bladder cell carcinoma type 5637 which was cultured in the laboratory. In this study, the study group was divided into 3 groups: untreated control group, gemcitabine-carboplatin group, and the meloxicam-gemcitabine-carboplatin combination group, each group consist of 5 replications. To determine the dose of meloxicam, gemcitabine, carboplatin used and the time of apoptosis evaluation, cytotoxic tests were carried out using the MTT assay method. The time of apoptosis evaluation is carried out for 24 hours. Apoptosis was assessed using the Apoptotag reagent from Trevigen®. Observation of apoptosis characterized by a positive reaction (the color turning brown) against DNA strand damage using the TUNEL assay method. One Way ANOVA was used for comparative analysis of apoptosis between the group with a significant value of p<0.05. The analysis was continued with a post hoc test, to determine the differences in each group. Results: The mean of apoptosis in the control group, gemcitabine-carboplatin group, apoptosis and the meloxicam-gemcitabine-carboplatin combination group was 0.748%, 80.336%, and 83.312%, respectively. Post hoc Bonferroni analysis showed that the results had significant difference between the meloxicam-gemcitabine-carboplatin combination group compared to the gemcitabine-carboplatin group (p=0.026) and the control group (p=0.000). Conclusion: Meloxicam-gemcitabine-carboplatin combination therapy has a significantly higher apoptotic effect than gemcitabine-carboplatin alone.